The field efficacy of Nigella sativa and Berberis vulgaris methanolic extracts against Haemoproteus columbae - Mostafa Razavi; Mohammad Asadpour; Hossein Malekpour; Arash Jafari (Mashhad University of Medical Sciences, 2018)
Objective: The methanolic extracts of Nigella sativaL. seeds (MENS) and Berberis vulgaris L.(MEBV) were investigated for treatment of Haemoproteus columbae-infected pigeons (Columba livia domestica). Materials and Methods: One hundred twenty naturally-infected pigeons were randomly divided into four groups of thirty each. Two groups were treated separately with the extracts, while the positive and negative control groups were given buparvaquone (Butalex®) and distilled water, respectively. The parasitaemia rate was calculated in all groups before and after the experiment at four-day intervals for16 days. Results: The results showed a high therapeutic effect for MENS with a progressive decrease in average parasitaemia rate from 18.17% before treatment to 0.73% at the end of treatment (p